2014
DOI: 10.1097/phm.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation to Primary Motor Area Improves Hand Dexterity and Selective Attention in Chronic Stroke

Abstract: Twenty minutes of cathodal tDCS to M1nonlesioned can promote both paretic hand dexterity and selective attention in people with chronic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
3
26
0
1
Order By: Relevance
“…In the absence of published data on this topic, the statistical outcomes of this study can serve in understanding and guiding the therapies of altered dexterity in MS patients. Previous tDCS studies addressing dexterity in stroke patients adopted sample sizes between 10 and 19 and yielded statistical significance [59,60].…”
Section: Sample Size Randomization and Blinding Effectivenessmentioning
confidence: 99%
“…In the absence of published data on this topic, the statistical outcomes of this study can serve in understanding and guiding the therapies of altered dexterity in MS patients. Previous tDCS studies addressing dexterity in stroke patients adopted sample sizes between 10 and 19 and yielded statistical significance [59,60].…”
Section: Sample Size Randomization and Blinding Effectivenessmentioning
confidence: 99%
“…Since tDCS is highly portable and safe, as well as economical, it can be used conveniently for the purposes of research and treatment3 ) . Previous studies have reported that providing tDCS to patients with stroke can help increase hand function, balance, and motor function in addition to improvements in cognition, such as executive function, concentration, short-term memory, and a reduction in depression4,5,6,7 ) . However, few studies have been conducted on the effect of tDCS on visual perception and performance of ADLs, which are important indices for improvement in the rehabilitation of patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Research has already shown that anodic tDCS can benefit patients with chronic stroke 7 . A study in stroke survivors showed that anodic tDCS can also improve selective attention 15 . Also, tDCS application over time improved motor skill learning with a paretic upper limb and resulted in prolonged shaping of brain activation, which supported behavioral enhancements in stroke patients 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, controversial findings in research have been reported about tDCS effects on post-stroke depression. For example, in two studies conducted by researchers, the positive effects of anodic tDCS in 522 and 141 patients with chronic stroke were studied; it was observed that the use of this method was able to create positive changes in attitude towards life and hope for life 3,15,16 . On the other hand, some studies of this group of patients who used anodic tDCS to reduce the negative effects of depression showed that this method was not able to produce specific and positive effects in reducing the complications of poststroke depression 17 .…”
Section: Introductionmentioning
confidence: 99%